Relationship of population of Velbar, Sarmatian and Chernyakhov cultures on the territory of Western Podillia in the second quarter of the 1st millennium AD - Onyshchuk, Jaroslav I. (Journal of the Belarusian State University. History, 2018)
Problems of the German-Sarmatian influence on the formation of the Chernyakhov culture of the Western Podillya were considered. Despite the political dominance of the Gothic Union («The States of Hermanarich») outside Velbar tribes had been subjected to the processes of cultural assimilation soon and mostly were gradually dissolved in the polyethnic Chernyakhov background, becoming one of its components. However, on the Volyn territory, as well as in the northern part of the Podolsky Upland, the Velbar population still managed to preserve their identity in house building, stucco molding and in their spiritual culture elements until the end of late-Romanesque period. A significant role in the formation of the Chernyakhov culture of the Western Podolia was played by the Sarmatians, who reached the areas of the Middle Dniester and its left tributaries in the second quarter of the 1st millennium AD. Their presence here was recorded in form of specific elements of burial rites in some Cherniakhov burial grounds, as well as in form of findings of individual items in the Velbar and Chernyakhov settlements, by anthropological research. A feature of the investigated region is also the presence of the Slav population, known as the «Upper Dniester Local Group of Chernyakhov Culture» in its west. The German-Slavic relationship still needs to be studied but recent research suggest an existence of a contact area of frontier type separating the tribal living territories.
Keywords: late-Romanesque period; Velbar culture; Chernyakhov culture; Cherepin-Teremtsi group; Sarmatians; Germans; Slavs; contact area; relationships; Western Podillya